ANALISIS PENDETEKSIAN HERDING BEHAVIOUR PADA BURSA SAHAM EMERGING DAN DEVELOPED MARKET ASIA (Negara Indonesia, China, Singapura dan Jepang) TAHUN 2012-2016 - Sendy, Hana; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2017)
Herding behaviour is one of investor’s irrasional behaviour that investors make decisions by following other investors' decisions or following a market consensus and tend not to use their own analysis in making their investment decisions. Herding behavior can affect the stability of the stock market because the market index value in the stock market will lead to a new price equilibrium, so it does not reflect the economic condition.This research tries to detect whether there is any herding behavior by investors in emerging market and developed market, which are Indonesia, China, Singapore and Japan stock exchange. By looking at the relationship between Cross Sectional Absolute Deviation (CSAD) and market return, the herding behavior on the stock market can be known. This study used a quantile regression analysis because detection of herding was done under different conditions of market. Which the condition is market stress normal and high return.The results of this study shows that herding behavior detected on the emerging market which is Indonesia and China stock market on the high return market condition, that means investors on the emerging market stock exchange do herding so it can be concluded investors in emerging market has an irrational behavior. While herding behaviour not detected on the developed market which is Japan an Singapore stock market, that means investors on the developed market country has a rational behavior